PENERAPAN MODEL PEMBELAJARAN MAKE A MATCH BERBANTUAN MEDIA FLASH CARD UNTUK MENINGKATKAN KETERAMPILAN MEMBACA DAN MENULIS HURUF JAWA DI SD - Hidayatur Rohmah; Khamdun; Wawan Shokib Rondli (STKIP Subang, 2023)
This research is motivated by the problem of a lackof learning media and students having difficulty distinguishing the forms of the Javanes script si that the skills in reading and writing Javanes letters are low in learning Javanes at SDN 4 Bategede. The purpose of this study was toimprove reading and writing skills in Javanese letters through make a match leraning with the helpof flash card media for elementary school students. This research is a classroom action research consisting of two cycles, each cycle consisting of planning, actin, observation, and reflection. The research subject were 20 students consisting of 8 male and 12 female students of class V SDN 4 Bategede. Data collection techniques include interviews, observation sheets and tests, as well as documentation. Data analysis used is qualitatitve and quantitative. From the results of the study it was found that the students reading and writing skills in pre-cycle Javanese letters received a score 52% in the less category. The results of the research cycle I showed that the application of the make a match learning model assisted by flash card media succeeded in increasing reading and writing Javanese letters with a score of 65% in the good category. In cycle II, the reading and writing sill sheets of Javanese letters managed to increase with a skill score of 84% in very good category. The results of the research on the achievement of the KKM percentage evaluation test increased from 60% in cycle I, the increasdes to100% in cycle II so that it can be concluded that the application of the Make A Match learing model assisted by Flash Card media can improve reading and writing skills in Javanes letters for V students SDN 4 Bategede.